2009
DOI: 10.2353/ajpath.2009.081012
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Course of Experimental Autoimmune Encephalomyelitis in PD-1-Deficient Central Nervous System Myelin Mutants

Abstract: It is assumed that the onset and course of autoimmune inflammatory central nervous system (CNS) disorders (eg, multiple sclerosis) are influenced by factors that afflict immune regulation as well as CNS vulnerability. We challenged this concept experimentally by investigating how genetic alterations that affect myelin (primary oligodendrocyte damage in PLPtg mice) and/or T-cell regulation (deficiency of PD-1) influence both the onset and course of an experimental autoimmune CNS inflammatory disease ͓MOG 35-55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…injections of pertussis toxin (PTX), which is assumed to induce a strong innate immune response leading to MOG-specific T-cell priming. In agreement with previous reports (12,14), the induction of EAE with this treatment resulted in accelerated disease progression in PD-1 −/− mice, characterized by earlier disease onset and an earlier peak in disease activity (Fig. 1A).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…injections of pertussis toxin (PTX), which is assumed to induce a strong innate immune response leading to MOG-specific T-cell priming. In agreement with previous reports (12,14), the induction of EAE with this treatment resulted in accelerated disease progression in PD-1 −/− mice, characterized by earlier disease onset and an earlier peak in disease activity (Fig. 1A).…”
Section: Resultssupporting
confidence: 80%
“…It has been demonstrated that ligand engagement of PD-1 inhibits T-cell activation, expansion, and cytokine production (17)(18)(19). Similarly, in EAE, PD-1 signaling in CNS-specific helper T cells may inhibit their expansion and secretion of inflammatory cytokines (10)(11)(12). Recently, T-helper 17 (Th17) cells were shown to be involved in EAE by producing IL-17 and GM-CSF (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…B7-H1 is constitutively expressed on different immune cells and can be inducibly expressed on many parenchymal cells (14)(15)(16)(17)(18) is crucially involved in maintenance of immunological tolerance (19,20). PD-1 has been identified as the canonical receptor for B7-H1 and is inducibly expressed on activated lymphocytes (21).…”
mentioning
confidence: 99%
“…With regard to the first aspect, we addressed the impact of lack of B7-H1 on either APCs or CD4 + T cells by performing coculture assays of MOGspecific B cells and MOG-specific CD4 + T cells in the presence of recombinant MOG protein and observed that B7-H1 was completely dispensable on antigen-presenting B cells but augmented CD4 + T-cell expansion and effector functions when lacking on the T-cell side. The B7-H1-PD-1 pathway has received major attention over the last years as a key component of the B7-homologs involved in the regulation of immune tolerance, tumor surveillance, and autoimmunity (18,(23)(24)(25). Despite its well-known role in immune regulation by APCs via interaction with its canonical receptor PD-1 on T cells, only a few studies so far have investigated the relevance of B7-H1 on T cells: Talay et al observed that expression of B7-H1 was required for T-cell-mediated conditioning of dendritic cell maturation in the context of infections (26).…”
Section: Discussionmentioning
confidence: 99%